Determination of oligomeric states of peptide complexes using thermal unfolding curves. Issue 2 (March 2015) - Rabe, Martin; Boyle, Aimee; Zope, Harshal R.; Versluis, Frank; Kros, Alexander
ABSTRACT: In their native form peptides are often found as oligomeric complexes, meaning they consist of more than one peptide chain. Coiled coils and helical bundles are common examples of such complexes. Their oligomeric state needs to be known precisely as this tremendously influences their biochemical and biophysical properties. The extensive analysis of circular dichroism spectroscopic data is commonly used to investigate the thermodynamics of binding and folding of these complexes. Here we present FitDis! an easy‐to‐use programme, which fits the most common two‐state unfolding transition to the measured thermal unfolding curves of any oligomer of any stoichiometry. We demonstrate, with simulated and real examples, that the comparison of different stoichiometric models fitted to the same dataset reveals the oligomeric states of these complexes along with detailed thermodynamic information. This method will significantly ease the analysis of and increase the amount of information gained from, the thermal unfolding curves of peptide complexes. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 65–72, 2015.